2019
DOI: 10.3389/fmolb.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

MARTINI-Based Protein-DNA Coarse-Grained HADDOCKing

Abstract: Modeling biomolecular assemblies is an important field in computational structural biology. The inherent complexity of their energy landscape and the computational cost associated with modeling large and complex assemblies are major drawbacks for integrative modeling approaches. The so-called coarse-graining approaches, which reduce the degrees of freedom of the system by grouping several atoms into larger “pseudo-atoms,” have been shown to alleviate some of those limitations, facilitating the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Given the improvements in accuracy in Martini 3, another key advantage of CG models in general is their computational performance. For instance, Martini CG based docking of biomolecular complexes can be around one order of magnitude faster compared to atomistic models, as recently demonstrated for the Haddock program 79,80 . Benchmarks tests performed with the program package Gromacs (version 2018) 81 showed that Martini based MD simulations of protein-ligand systems can be 110-350 times faster than all-atom simulations, with the performance gain increasing with growing system size (see Supplementary Discussion and Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 83%
“…Given the improvements in accuracy in Martini 3, another key advantage of CG models in general is their computational performance. For instance, Martini CG based docking of biomolecular complexes can be around one order of magnitude faster compared to atomistic models, as recently demonstrated for the Haddock program 79,80 . Benchmarks tests performed with the program package Gromacs (version 2018) 81 showed that Martini based MD simulations of protein-ligand systems can be 110-350 times faster than all-atom simulations, with the performance gain increasing with growing system size (see Supplementary Discussion and Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 83%
“…However, the oxDNA/oxRNA models only allow for representation of nucleic acids alone, limiting their scope of usability. While there have been coarse-grained simulation models developed for protein-DNA interactions, [31][32][33][34][35][36][37] none are able to be directly used with the oxDNA model. The development of an efficient tool compatible with oxDNA would allow for efficient study of arbitrary protein-DNA complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the structures predicted by the all atom model, it has been confirmed that the MARTINI force field not only accelerates the simulation process by about three orders, but also preserves the characteristics of different amino acids, as the all atom model also does. The comparisons between the structures predicted by the MARTINI CG and all atom models can be also seen for a peptide-bilayer system 32 , DNA 33 , and DNA–protein complexes 34 , which show good reproductively of the CG model to those by the AA model.…”
Section: Introductionmentioning
confidence: 79%